Improving the waiting time in outpatient clinics using lean approach in hospital: a systematic review - Albalawi, Majed; Mahmud, Aidalina; Manaf, Rosliza Abdul; Mohd Nazan, Ahmad Iqmer Nashriq; Aljohani, Ahmad; Mohamad, Aslah (Universiti Putra Malaysia Press, 2024)
Introduction: The use of the lean approach in healthcare has rapidly gained popularity globally, although this approach was more routinely used in the manufacturing sector as opposed to health. Besides, recent studies confirm the suitability of the lean approach applications for improving the quality of medical care. This study aimed to determine the Lean approach’s capacity to improve the waiting time in outpatient clinics in hospitals. Methods: The systematic review approach was employed to help in the research procedures. Search databases used included Ovid, Google scholar, PubMed, MEDLINE, and archive. Besides, search terminologies such as the Lean approach, Hospital-implementation, waiting time, and patient flow were used to help identify sources that best suited the investigation process. Results: The review revealed that the lean approach is suitable for the reduction of waiting times as well as for improving efficiency in the clinic. The outcomes provide a basis for reducing the average waiting time within the hospital. Conclusion: This study recommended that healthcare facilities and departments should take a keen interest in implementing the Lean approaches, as they are crucial for reducing waiting time.